2020
DOI: 10.1101/2020.08.01.20166371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcome of COVID-19 with co-existing surgical emergencies in children: our initial experiences and recommendations

Abstract: Background: COVID 19 has changed the practice of surgery vividly all over the world. Pediatric surgery is not an exception. Prioritization protocols allowing us to provide emergency surgical care to the children in need while controlling the pandemic spread. The aim of this study is to share our experiences with the outcome of children with COVID 19 who had a co existing surgical emergency. Methods: This is a retrospective observational study. We reviewed the epidemiological, clinical, and laboratory data of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Our findings confirm that SARS-CoV-2 can infect neonates and that the majority of these infections occur 17 Case report France a PR 6 Good Aghdam 18 Case report Iran PR 4 Intermediate Alonso Diaz 19 Case report Spain PR 5 Intermediate Alzamora 20 Case report Peru PR 3 Intermediate Ayed 21 Case series Kuwait Preprint 1 Low Banerjee 22 Case series India PR 2 Low Barbero 23 Retrospective cohort study Spain PR n.a. Intermediate Buonsenso 24 Case series Italy PR 4 Intermediate Carosso 25 Case report Italy PR 4 Intermediate Chacon-Aguilar 26 Case report Spain PR 5 Intermediate Coronado Munoz 27 Case report USA PR 4 Intermediate Demirjian 28 Case report UK PR 4 Intermediate Dong 29 Case report China PR 6 Good Dumpa 30 Case report USA PR 6 Good Eghbalian 31 Case report Iran PR 4 Intermediate Feng 32 Case series China PR 3 Intermediate Fenizia 33 Case series Italy PP 5 Intermediate Ferrazzi 34 Case series Italy PR 1 Low Garazzino 35 Case series Italy PR 2 Low Gonzales Brabin 36 Case report Spain PR 3 Intermediate Gordon 37 Case report UK PR 2 Low Gregorio-Hernandez 38 Case series Spain PR 5 Intermediate Groß 39 Case series Germany PR 5 Intermediate Han 40 Case report South Korea PR 6 Good Hantoushzadeh 41 Case series Iran PR 6 Good Hasan 42 Case series Bangladesh Preprint 6 Good Hu 43 Case series China PR 6 Good Ibarra Rios 44 Case report Mexico Preprint 5 Intermediate Kanburoglu 45 Case report Turkey PR 1 Low Kayem 46 Case series France PR 1 Low Kirtsman 47 Case report Canada PR 6 Good Knight 48 Retrospective cohort study UK PR n.a. n.a.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirm that SARS-CoV-2 can infect neonates and that the majority of these infections occur 17 Case report France a PR 6 Good Aghdam 18 Case report Iran PR 4 Intermediate Alonso Diaz 19 Case report Spain PR 5 Intermediate Alzamora 20 Case report Peru PR 3 Intermediate Ayed 21 Case series Kuwait Preprint 1 Low Banerjee 22 Case series India PR 2 Low Barbero 23 Retrospective cohort study Spain PR n.a. Intermediate Buonsenso 24 Case series Italy PR 4 Intermediate Carosso 25 Case report Italy PR 4 Intermediate Chacon-Aguilar 26 Case report Spain PR 5 Intermediate Coronado Munoz 27 Case report USA PR 4 Intermediate Demirjian 28 Case report UK PR 4 Intermediate Dong 29 Case report China PR 6 Good Dumpa 30 Case report USA PR 6 Good Eghbalian 31 Case report Iran PR 4 Intermediate Feng 32 Case series China PR 3 Intermediate Fenizia 33 Case series Italy PP 5 Intermediate Ferrazzi 34 Case series Italy PR 1 Low Garazzino 35 Case series Italy PR 2 Low Gonzales Brabin 36 Case report Spain PR 3 Intermediate Gordon 37 Case report UK PR 2 Low Gregorio-Hernandez 38 Case series Spain PR 5 Intermediate Groß 39 Case series Germany PR 5 Intermediate Han 40 Case report South Korea PR 6 Good Hantoushzadeh 41 Case series Iran PR 6 Good Hasan 42 Case series Bangladesh Preprint 6 Good Hu 43 Case series China PR 6 Good Ibarra Rios 44 Case report Mexico Preprint 5 Intermediate Kanburoglu 45 Case report Turkey PR 1 Low Kayem 46 Case series France PR 1 Low Kirtsman 47 Case report Canada PR 6 Good Knight 48 Retrospective cohort study UK PR n.a. n.a.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline demographics of trial groups are shown in table (1).Groups included 419 patients, 212 (50.6%) of them were males and 207 (49.4%) females.The age groups ranged from (13)(14)(15)(16)(17)(18) to (> 65) years.Table (2) showed the effectiveness of black seeds on covid-19 among the participants. Cross tabulation was performed to describe the association between black seeds group and severity as well as the final outcome of infection with covid19.…”
Section: Resultsmentioning
confidence: 99%
“…COVID19 storm shows its lethal face worldwide and it is still difficult to predict how long it will last, and how deadly it could be (1) . This disease mainly affected social life, particularly health care services in addition to daily treatment practices since the world health organization (WHO) declared SARS CoV-2 as a global pandemic in early 2020 (2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%